2021
DOI: 10.1021/acs.orglett.1c01931
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed anti-Carbosilylation of Alkynes to Access Isoquinolinone-Containing Exocyclic Vinylsilanes

Abstract: A Pd-catalyzed trans-selective carbosilylation reaction of alkynes has been developed. The trans-vinylpalladium species, generated through intramolecular syn-carbopalladation of alkynes and subsequent cis-trans isomerization, were captured by hexamethyldisilane to form multisubstituted vinylsilanes. This reaction provides a useful strategy for the stereoselective synthesis of isoquinolinone-containing exocyclic tetrasubstituted vinylsilanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 79 publications
(17 reference statements)
0
16
0
Order By: Relevance
“…For example, Takemoto, Player, Suffert, Van der Eycken and others developed the palladium-catalyzed cis -selective annulation of internal alkynes, followed by their arylation, 3 alkenylation, 3 a , e and heteroarylation 4 (Scheme 1a, Path a). Palladium-catalyzed trans -selective cyclization of internal alkynes and sequential silylation, 5 amination, 6 alkynylation 7 were disclosed by Zhang, Shang and Müller (Scheme 1a, Path b). The palladium-catalyzed alkyne cyclization/carbohalogenation was achieved by the Lautens group (Scheme 1a, Path c).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Takemoto, Player, Suffert, Van der Eycken and others developed the palladium-catalyzed cis -selective annulation of internal alkynes, followed by their arylation, 3 alkenylation, 3 a , e and heteroarylation 4 (Scheme 1a, Path a). Palladium-catalyzed trans -selective cyclization of internal alkynes and sequential silylation, 5 amination, 6 alkynylation 7 were disclosed by Zhang, Shang and Müller (Scheme 1a, Path b). The palladium-catalyzed alkyne cyclization/carbohalogenation was achieved by the Lautens group (Scheme 1a, Path c).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Zhang et al have also demonstrated their work on palladium-catalyzed anticarbosillylation of alkynes 162 using hexamethyldisilane 163 to afford isoquinoline-containing exocyclic vinylsilanes 164 (Scheme 55). 66 The reaction was carried out with different substituted substrates to determine the generality of the demonstrated reaction condition. Substrates containing electron-rich groups proved to be more successful than their electron-withdrawing group containing analogs.…”
Section: Scheme 43 Rhodium Catalyzed Formal C-o Insertion Reaction Fo...mentioning
confidence: 99%
“… 1 9 Such reactions have been performed in either intra- or intermolecular fashion, with the resulting alkenyl-Pd intermediate being coupled afterward with different species, such as boronic acids, 10 12 organotin reagents, 13 18 and C -, 19 N -, 20 , 21 and O -nucleophiles, 22 among many others ( a , Scheme 1 ). 23 28 …”
Section: Introductionmentioning
confidence: 99%